1997
DOI: 10.1126/science.276.5316.1265
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine: A Mediator of the Sleep-Inducing Effects of Prolonged Wakefulness

Abstract: Both subjective and electroencephalographic arousal diminish as a function of the duration of prior wakefulness. Data reported here suggest that the major criteria for a neural sleep factor mediating the somnogenic effects of prolonged wakefulness are satisfied by adenosine, a neuromodulator whose extracellular concentration increases with brain metabolism and which, in vitro, inhibits basal forebrain cholinergic neurons. In vivo microdialysis measurements in freely behaving cats showed that adenosine extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
739
1
8

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,091 publications
(767 citation statements)
references
References 34 publications
19
739
1
8
Order By: Relevance
“…The stimulant effects of caffeine on the central nervous system at doses obtained through normal human consumption are due to caffeine's ability to antagonize adenosine receptors (Fredholm et al, 1999). Numerous reports have corroborated that adenosine is a neuromodulator that is involved in sleep regulation Benington et al, 1995;Porkka-Heiskanen et al, 1997;Radulovacki et al, 1982Radulovacki et al, , 1985Satoh et al, 1996Satoh et al, , 1999Scammell et al, 2001;Schwierin et al, 1996;Strecker et al, 2000;Ticho and Radulovacki, 1991;Urade et al, 2003). It has recently been proposed that in humans, caffeine mimics the effects of a reduction in sleep homeostasis during prolonged wakefulness (Landolt et al, 2004).…”
Section: Discussionmentioning
confidence: 97%
“…The stimulant effects of caffeine on the central nervous system at doses obtained through normal human consumption are due to caffeine's ability to antagonize adenosine receptors (Fredholm et al, 1999). Numerous reports have corroborated that adenosine is a neuromodulator that is involved in sleep regulation Benington et al, 1995;Porkka-Heiskanen et al, 1997;Radulovacki et al, 1982Radulovacki et al, , 1985Satoh et al, 1996Satoh et al, , 1999Scammell et al, 2001;Schwierin et al, 1996;Strecker et al, 2000;Ticho and Radulovacki, 1991;Urade et al, 2003). It has recently been proposed that in humans, caffeine mimics the effects of a reduction in sleep homeostasis during prolonged wakefulness (Landolt et al, 2004).…”
Section: Discussionmentioning
confidence: 97%
“…Adenosine accumulates in certain areas of the brain when neurons consume energy in the form of ATP during prolonged wakefulness. In animal studies, adenosine levels in the brain increased during sleep deprivation and returned to baseline during sleep [14], [25], [26] . Other substances hypothesized to be involved in promoting sleep and contributing to the homeostatic factor include proinflammatory cytokines (interleukin-1) [18], [27] prostaglandin D 2 , and growth hormone-releasing hormone [27] .…”
Section: Neurotransmitters Involved In Sleep and Wakefulnessmentioning
confidence: 98%
“…Humans cannot remain awake voluntarily for longer than 2 to 3 days, and rodents cannot survive without sleep for longer than few weeks [10], [14] . The homeostatic factor represents an increase in the need for sleep (sleep pressure) with increasing duration of prior wakefulness.…”
Section: Homeostatic Regulation Of Sleepmentioning
confidence: 99%
“…Thus, cholinergic nuclei of the mesopontine tegmentum (Ch 5 -Ch 6 nuclei, according to the nomenclature of Mesulam et al (1983)) are tonically inhibited by adenosine through an action onto A 1 receptors (Rainnie et al 1994). Prolonged wakefulness is associated to enhanced adenosine concentrations in the basal forebrain (Porkka-Heiskanen et al 1997) as a result of local brain metabolism; moreover, induction of SW sleep is associated to increased levels of adenosine in brain (Strecker et al 2000). On this basis it has been suggested that adenosine is an endogenous sleep factor (Strecker et al 2000) and modulates EEGarousal through ACh projections to the cortex (Portas et al 1997;Rainnie et al 1994;Strecker et al 2000).…”
mentioning
confidence: 99%